2005
DOI: 10.1002/ajmg.a.30106
|View full text |Cite
|
Sign up to set email alerts
|

An interstitial deletion of chromosome 7 at band q21: A case report and review

Abstract: We report on a girl with moderate developmental delay and mild dysmorphic features. Cytogenetic investigations revealed a de novo interstitial deletion at the proximal dark band on the long arm of chromosome 7 (7q21.1-q21.3) in all analyzed G-banded metaphases of lymphocytes and fibroblasts. Fluorescence in situ hybridization (FISH) and molecular studies defined the breakpoints at 7q21.11 and 7q21.3 on the paternal chromosome 7, with the proximal deletion breakpoint between the elastin gene (localized at 7q11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 35 publications
4
33
1
Order By: Relevance
“…Intermediate interstitial deletion of chromosome 7 spanning from q22 to q31 bands is rare and causes multiple congenital malformations in the affected children (26,27). Only a few rare prenatally detected cases presenting with fetal growth retardation and ultrasonographic findings such as cranial malformations, syndactyly in the lower extremities, renal pelvic dilatation,…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate interstitial deletion of chromosome 7 spanning from q22 to q31 bands is rare and causes multiple congenital malformations in the affected children (26,27). Only a few rare prenatally detected cases presenting with fetal growth retardation and ultrasonographic findings such as cranial malformations, syndactyly in the lower extremities, renal pelvic dilatation,…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 patients with cytogenetically visible interstitial deletions of 7q21-q22 [Fukushima et al, 2003;Courtens et al, 2005;Manguoglu et al, 2005], and one patient with a microdeletion in 7q21.3 [Wieland et al, 2004] have been reported to date. Among other clinical problems (mental retardation, short stature, microcephaly, hearing loss), split hand/split foot malformation was a common feature in patients with deletions of subbands 7q21.3 and 7q22.1.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, cardiomegaly was also detected on sonographic evaluation. Although cardiac anomalies are not commonly associated with interstitial chromosome 7q deletion, postnatally detected ventricular septal defects and pulmonary stenosis were reported [6,12,15] . We were unable to attribute a specific cause for the cardiomegaly due to the limitations of sonographic resolution and lack of postmortem assessment (deferred by the parents).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with intermediate interstitial deletion of chromosome 7q have characteristic prenatal and postnatal phenotypes including abnormal skull shape, microcephaly, flat nasal bridge, cleft palate, teeth anomalies, ear malformations, facial dysmorphism, micrognathia, cardiac anomalies, genital anomalies, ectrodactyly, fetal growth restriction, glaucoma, hearing loss, feeding problems, mental retardation and developmental delay [6][7][8][9][10][11][12][13] . Amongst these, fetal growth restriction and developmental delay/mental retardation are the most common, while ectrodactyly is reported in half the cases [6] . Except for the presence of ectrodactyly, our case displayed the characteristic phenotypical features: fetal growth restriction, wide nasal bridge, low-set ears and cleft palate while prominent cheeks and nuchal skin had never been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation